Pengaruh Aplikasi Nanobiostimulan Rumput Laut (Padina minor Yamada) terhadap Kadar Klorofil Kedelai (Glycine max (L.) Merr.) - Shayen, Millania Putri; Noli, Zozy Aneloi; Maideliza, Tesri; Suwirmen, Suwirmen (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Chlorophyll is a green pigment in plants which is important for the process of photosynthesis. The photosynthesis process affects plant growth. Seaweed extract has been proven to be a source of biostimulants that can increase plant growth, one of which is Padina minor. Concentration and frequency are important factors that influence the work of biostimulants. One effort to increase the effectiveness of biostimulants is by changing the crude extract into the form of nanoparticles. This research aims to analyze the effect of concentration, frequency, and interaction between concentration and frequency of crude extract and Padina minor nano extract on chlorophyll levels in soybean plants. The method used was a completely randomized design (CRD) in factorial consisting of 2 factors and 4 replications. Factor A concentration of Padina minor extract, namely control, crude extract 0.4%, nano extract 0.2%, 0.3%, 0.4%, 0.5% and 0.6%. Factor B is the frequency of administration of Padina minor extract, namely 1, 2, and 3 times administration. Based on research that has been carried out, the results showed that administration of 0.4% crude extract increased the average chlorophyll a level by 6.6% and a total of 11%. Meanwhile, chlorophyll b gave the same results as 0.3% nano extract, namely an increase of 14% compared to the control. The total frequency of administration of Padina minor extract was 3 times, and the same as the other treatments, increasing chlorophyll a levels by 4.6%, b by 5.2%, and a total of 4.9% compared to the control. The interaction between concentration and frequency of administration of Padina minor nano extract gives the same results as the crude extract, with lower concentration and less frequency of application in increasing levels of chlorophyll a, chlorophyll b, and total chlorophyll in soybean plants.